Implementation of Locally Oriented PBL Devices on The Other Reaction to the Students' Critical Thinking Ability - Jenny I. Laroni; Afadil Afadil; Paulus H. Abram (Jurnal Akademika Kimia, 2024)
This study aims to determine the validity, practicality, and effectiveness of the application of problem-based learning tools with local wisdom-oriented material on the rate of reaction to the critical thinking skills of students of SMAN 1 Pamona Utara. The research design used a one-group pretest-posttest design. The population of all class XI MIPA students at SMAN 1 Pamona Utara. The research sample consisted of 54 people, comprising 27 class XI MIPA 1 students and 27 class XI MIPA 2 students, with the two classes serving as the experimental classes. Experts carried out the validation of learning tools, and the score of each validity item of the research instrument in the form of lesson plans and worksheets, calculated according to a Likert scale, was 74.10%, indicating that the lesson plans and worksheets were declared valid and fit for use based on validity by the validator. For the practicality assessment instrument, the implementation of the RPP Problem-Based Learning has been carried out well, resulting in a score of 91.3%, which falls in the very high category. In contrast, the assessment instrument for the effectiveness of critical thinking skills is very high, which is divided into Interpretation, Evaluation, and Analysis, namely, class XI MIPA 1 scored 93%, 96.25%, and 96.5%, and class XI MIPA 2 had scores of 95%, 95.50%, and 96.5%. The value of student learning outcomes is evident in the N-gain values for both classes XI MIPA 1 and 2, which are 0.76 and 0.74, respectively, placing them in the high category. In LKPD based on local cultural wisdom, students are expected to improve their conceptual understanding of the subject matter.